STRATEGIES FOR DEVELOPING LISTENING COMPREHENSION SKILLS IN PRIMARY SCHOOL LEARNERS IN ENGLISH LANGUAGE TEACHING - Xolmatova Hamrobi Shermurod qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract, This article explores strategies for developing listening comprehension skills in primary school learners within the context of English language teaching (ELT). Listening comprehension is a vital skill in language acquisition, and its development is essential for effective communication. This paper examines various practical methods and techniques that teachers can apply to improve listening comprehension in young learners.